Congenital myopathies: clinical phenotypes and new diagnostic tools - Denise Cassandrini; Rosanna Trovato; Anna Rubegni; Sara Lenzi; Chiara Fiorillo; Jacopo Baldacci; Carlo Minetti; Guja Astrea; Claudio Bruno; Filippo M. Santorelli; the Italian Network on Congenital Myopathies (BMC, 2017)
Abstract Congenital myopathies are a group of genetic muscle disorders characterized clinically by hypotonia and weakness, usually from birth, and a static or slowly progressive clinical course. Historically, congenital myopathies have been classified on the basis of major morphological features seen on muscle biopsy. However, different genes have now been identified as associated with the various phenotypic and histological expressions of these disorders, and in recent years, because of their unexpectedly wide genetic and clinical heterogeneity, next-generation sequencing has increasingly been used for their diagnosis. We reviewed clinical and genetic forms of congenital myopathy and defined possible strategies to improve cost-effectiveness in histological and imaging diagnosis.